Oxidative Modifications of RNA and Its Potential Roles in Biosystem - Tanaka, Mikiei; Chock, P. Boon (Frontiers in Molecular Biosciences, 2021)
Elevated level of oxidized RNA was detected in vulnerable neurons in Alzheimer patients. Subsequently, several diseases and pathological conditions were reported to be associated with RNA oxidation. In addition to several oxidized derivatives, cross-linking and unique strand breaks are generated by RNA oxidation. With a premise that dysfunctional RNA mediated by oxidation is the pathogenetic molecular mechanism, intensive investigations have revealed the mechanism for translation errors, including premature termination, which gives rise to aberrant polypeptides. To this end, we and others revealed that mRNA oxidation could compromise its translational activity and fidelity. Under certain conditions, oxidized RNA can also induce several signaling pathways, to mediate inflammatory response and induce apoptosis. In this review, we focus on the oxidative modification of RNA and its resulting effect on protein synthesis as well as cell signaling. In addition, we will also discuss the potential roles of enzymatic oxidation of RNA in mediating cellular effects.